Safe Concentration of Benzene Exposure Based on Safe Human Dose of Workers in The Paint Manufacturing Industry Sidoarjo, East Java, Indonesia - Ayu Prima Kartika1, Vivi Budiarti1, Achmat Kuncoro1, Charles Kimura1, Abdul Rohim Tualeka2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Manufacture of paints using benzene in large quantities in the products they produce. Workers in the paint industry may face an increased risk of high health complications. The purpose of this study was to determine the levels of safe concentration of benzene for workers in the Paint Manufacturing Industry in Sidoarjo East Java, Indonesia. Methods: This research was conducted using a cross sectional method. The sample in this study were 24 respondents. The variables that became the data of this study included benzene concentration (C) time of daily exposure (tE), frequency of annual exposure (fE), duration of exposure (Dt), height (cm), weight (kg), age, respiration rate (BR), body surface area, weight of white rat, body surface of white rat, highest dose of toxin without effect on experimental animals (NOAEL), Km factor in animal (Animal Km), Km factor on workers (Human Km), safe limits for toxin doses for workers (SHD), and benzene concentrations in safe air for workers (C is safe). Data analysis in this study was carried out by using quantitative data analysis manually to determine the safe concentration of benzene for workers in the Paint Manufacturing Industry in Sidoarjo East Java, Indonesia. Results: Based on the results of measurements carried out, the concentration of benzene in the work environment of the Sidoarjo Paint Industry in the mixing solvent section is 2 ppm and in the packing section is 0.4 ppm, the safe concentration is 0.028 ppm. Conclusion: The recommended safe concentration of benzene exposure is 0.028 ppm. The safe concentration value exceeds the set value of 0.009 ppm daily for acute effects and 0.003 ppm daily for chronic effects, so control measures are needed to protect against the adverse effects of benzene on the health of workers. Control recommendations are to provide a good exhaust ventilation system at the paint manufacturing.